2020
DOI: 10.1002/jpen.2051
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Bowel Syndrome: Epidemiology, Hospitalization Trends, In‐Hospital Mortality, and Healthcare Utilization

Abstract: Introduction : Short-bowel syndrome (SBS) is a common cause of chronic intestinal failure and is associated with increased morbidity, mortality, poor quality of life, and an increased burden on healthcare costs. Methods: We used the US Nationwide Inpatient Sample database from 2005 to 2014. We identified adult SBS hospitalizations by using a combination of International Classification of Diseases, Ninth Revision, Clinical Modification codes. We studied the demographics of the patients with SBS and analyzed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 101 publications
0
32
0
Order By: Relevance
“…Patients with intestinal insufficiency (INS) and intestinal failure (IF) are categorized under short bowel syndrome (SBS) [23]. Recent data suggest 10% of the patients with SBS are malnourished [22], and 20%e44.6% have had a weight loss [22,24]. A study from 2017 of patients with IF found that 69% were at severe nutritional risk and 27% at moderate nutritional risk [25], further patients with IF have significant higher risk of being malnourished [26].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with intestinal insufficiency (INS) and intestinal failure (IF) are categorized under short bowel syndrome (SBS) [23]. Recent data suggest 10% of the patients with SBS are malnourished [22], and 20%e44.6% have had a weight loss [22,24]. A study from 2017 of patients with IF found that 69% were at severe nutritional risk and 27% at moderate nutritional risk [25], further patients with IF have significant higher risk of being malnourished [26].…”
Section: Introductionmentioning
confidence: 99%
“…SBS‐IF is rare, with an estimated prevalence in adults of 0.4–25.0 per million in the United States and in Europe, with prevalence increasing 6–9 . Recent improvements in management (notably owing to improved understanding of physiological changes and how to augment them to gain enteral autonomy) have improved the historically high morbidity and mortality of SBS‐IF 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…short bowel syndrome (SBS), and is connected to high mortality rates 1 . For LC patients, the prevalence of MN is indicated with up to 90% 2 ; for patients suffering from SBS with around 10 to 40% 3 . Disease-related MN is closely related to mild, chronic inflammation 4 .…”
Section: Introductionmentioning
confidence: 99%